THE IMPACT OF REGIONAL EXPANSION ON THE EFFECTIVENESS OF HEALTHCARE SERVICES - Ilmi, Iva Nur; Suryanto; Pramono, Retno Widodo Dwi (Built Environment Studies, 2025)
The enactment of Law Number 7 of 2002 concerning the Establishment of Penajam Paser Utara (PPU) Regency marked the official formation of this new administrative region, resulting from the separation of four sub-districts from the original twelve in Paser Regency. As a newly established regency, PPU required immediate development in institutional structures, government infrastructure, and development planning. A key indicator of progress lies in healthcare facility improvements, which were previously difficult to access due to reliance on water transport to Balikpapan or Paser. This study aims to analyze healthcare service development in PPU and assess how regional expansion has influenced service effectiveness. The research compares conditions before and after the expansion using a deductive qualitative approach, triangulation, and descriptive methods. Findings indicate that while the number of healthcare facilities declined, service utilization became more efficient, travel distances were reduced, and quality improved. Effective health service delivery depends on availability, accessibility, and continuity. While regional expansion positively affected specific dimensions, its most decisive influence was improved interaction between health workers and patients, disease prevention, and public health education.